The Development of Customary Doctrine of Rechtsverwerking: How to Ensure Legal Certainty in Land Registration? - Wiryawan, I Wayan; Budiartha, I Nyoman Putu; Sujana, I Gede (Udayana Journal of Law and Culture, 2025)
The doctrine of rechtsverwerking has been applied in the context of customary law related to land ownership in Indonesia for a long time. However, its application in the registration process did not ensure legal certainty. Therefore, this research reviewed the reformulation of the registration process to enhance the legal certainty of land ownership. This led to the use of diverse legal methods to examine relevant written laws and court decisions. Additionally, a hermeneutical approach was applied to understand the text and context of rechtsverwerking. In view of the discourse, the current legal framework on the land rights registration system lacks legal certainty. This led to the significance of enacting a new National Law on Lands, which offered greater certainty and broader regulations. This upcoming law is also expected to include provisions on compensation for errors made by land officials regarding the transfer of ownership.